Pacto universitário de educação em direitos humanos: seus antecedentes institucionais, implementação e impactos em IES privadas - Pelegrinelli, Gisela (Universidade do Vale do Rio dos Sinos, 2021)
Entitled "University Pact on Human Rights Education: its institutional background, implementation and impacts on private IES", This thesis work aims to explain the trajectory of public policies aimed at Education in Human Rights, with special attention to the most recent policy called Pacto Universitario em EDH, its spin-off from the implementation of the Pacto Universitario in two Higher Education Institutions. Due to political events, the work of the thesis also incorporated the dismantling of bodies aimed at EDH and the deinstitutionalization of the University Pact. In order to fulfill the proposed objectives, two case studies were used to meet the implementation of the University Pact in two Higher Education Institutions - private HEIs in the DF and the process of institutionalization and deinstitutionalization of public policies. This is a qualitative research based on a documental analysis. The work carried out a reconstruction of the institutions and actors that contributed to the constitution of the University Pact, seeking to illuminate the trajectory of public policies aimed at EDH, in addition to the design and implementation of national EDH plans and programs. It showed the creation of state EDH committees, the institution of the National Guidelines for Education in Human Rights (DNEDH) in 2012 by the National Council of Education (CNE), which, of a mandatory and binding nature, establishes EDH as one of the “axes fundamentals of the right to education” and designates the responsibility of education systems in their implementation, thus reinforcing an educational policy in the area of ​​human rights. This highlights a strategic action by the Brazilian government to implement EDH. The survey pointed out that the University Pact was an initiative that sought to correct gaps in the PNEDH and had a great impact on its launch, with massive adherence. In its institutionalization, as a public policy, it brought advances in view of the implementation scenario of the EDH in the HEIs that adhered to the cooperation agreement. However, the dismantling of SECADI and automatically the deinstitutionalization of the University Pact, meant less public educational policy in EDH. In the two HEIs surveyed, advances in the implementation of EDH from the Pact were evidenced, both in terms of structuring management tools and effective actions and in the perception of students about HD. It is noteworthy that the institution in which there were already actions in EDH, the Pact meant greater progress, which was committed to the end of this public policy.
Keywords: Educação em direitos humanos; Políticas públicas educacionais; Pacto universitário; Desinstitucionalização; IES privadas; Human rights education; Educational public policies; University pact; Deinstitutionalization; Private IES; ACCNPQ::Ciências Humanas::Sociologia